Implementation of Digital Transformation and Artificial Intelligence as Innovation for MSMEs in the Era of Industrial Revolution 4.0 - Pratama, Is Arianto; Adiningsih, Sri Hutami (Amirul Bangun Bangsa Publishing, 2024)
Technology plays an important role in economic development. Covid-19 has changed people's lifestyles and the behavioral patterns of business actors have transformed from traditional to digital. Even though Covid-19 has had a significant impact in the form of a decline in the global economy, including on Micro, Small and Medium Enterprises (MSMEs), it has also provided lessons in the form of adaptation to innovation and digital transformation in the form of the application of the latest technology and artificial intelligence. This research uses a qualitative descriptive method and research data is collected through articles, journals, books, and official sources that are reliable and accurate. This research aims to describe phenomena or events from the development of the Industrial Revolution 4.0 era which supports the growth of MSMEs to change or transform digitally with the help of artificial intelligence so that they can grow and compete globally. The results of this research show that the Industrial Revolution 4.0 and digital transformation can provide opportunities and strengths to build sustainable businesses. Along with changes in people's consumption patterns, MSMEs have also implemented digital adoption in the form of switching to e-commerce platform sites, food delivery applications, and online business models. However, the adoption of artificial intelligence is still not widely used by MSMEs. However, several MSMEs have adopted artificial intelligence technology such as chatbot applications for automatic customer communication services. Apart from that, support and providing programs from the government and the private sector are needed for MSMEs so that they can develop and adapt their business models to the latest technological adaptations so that MSMEs are also able to survive and even grow rapidly in the future.